The Role of Russia in the Development of Integration Processes in Emerging Markets - Kheyfets, Boris Aronovich; Chernova, Veronika Yurievna (Economy of Regions, 2020)
Due to post-crisis slowdown in globalization, there is a necessity to structurally transform the Russian economy, strengthen the existing strategic partnerships and explore new economic growth points. Thus, the paper substantiates the importance of Russia’s participation in macro-regional economic associations. We examine the problems and risks of partnership development between the countries. Based on a mutual trade significance index, we analyse the importance of trade between the Russian Federation and the countries of the Eurasian Economic Union (EAEU), BRICS (Brazil, India, China and South Africa), and Shanghai Cooperation Organisation (SCO). The analysis shows that the share of Russian trade with the BRICS and SCO countries is growing fastest, largely due to the trade with China. At the same time, for the economic growth of the EAEU member countries, intra-union trade is less beneficial than the development of foreign trade relations. Moreover, recently the EAEU partners of Russia have been more interested in establishing and developing relations with third countries. The EAEU countries face a variety of problems during the integration process, including the fundamental incompatibility of the interests of the participants. Based on the obtained results, we demonstrate the development prospects of cooperation between Russia and various integration associations. The main obstacle for establishing new economic unions is the low competitiveness of the Russian economy. Even though the current situation does not enhance inter-regional cooperation, it provides Russia an opportunity to strengthen cooperation in the Asia-Pacific region and increase its participation in multilateral mechanisms. We conclude that in the medium term EAEU has to focus on strengthening the existing institutions and creating a modern flexible economic partnership.